IMPORTANT FESTIVALS OF THE KRISHANAVAKKA COMMUNITY - A STUDY (International Journal of Food and Nutritional Sciences, 2022)
Krishnavakkas is a Malayalam speaking microscopic minority community mostly confined with the Kalkulam taluk of Kanyakumari District due to various reasons. The name Krishnavakkas was given by King Udaya Marthanda Varma, the Maharaja of Venadu (ancient Travancore) during the commencement of the Kollam Era also known as Malayalam Era (A.D. 825). Their fairs and festivals would give a fair idea about the socio-economic and religious life of the Krishnavakkas. The important festivals in a year are Onam, Vishu, Pongal, Deepavali and Krishna Jayanthi.